A comprehensive evaluation of efficacy of hyperbaric oxygen therapy in non-arteritic central retinal artery occlusion using enhanced depth imaging optical coherence tomography - Jung Min Lee; Se Hyun Choi; Gang Seok Jeon; In Boem Chang; Soon Joo Wang; In Hwan Hong (Scientific Reports, 2024)
Abstract This study aimed to assess the efficacy of hyperbaric oxygen therapy (HBOT) in patients with central retinal artery occlusion (CRAO) by analyzing changes in visual acuity (VA) and enhanced depth imaging optical coherence tomography (EDI-OCT) parameters. A comparative retrospective study was conducted by reviewing the medical records of all HBO-treated RAO patients in our department and comparing them with matched RAO patients who did not receive HBO treatment. All patients treated with HBO received treatment within 7 days of the onset of visual symptoms. Baseline characteristics were compared, and VA and OCT parameters were evaluated at baseline and follow-up visits. A total of 50 eyes from 50 patients were included, with 29 eyes in the HBOT group and 21 eyes in the control group. The mean BCVA of the HBOT group at the initial visit was 2.03 logMAR, which improved to 1.55 logMAR at 6 months, with the change being statistically significant (P < 0.01), while the control group's BCVA remained almost unchanged, from 2.1 to 2.11 logMAR (P = 0.762). The central choroidal thickness increased significantly in the HBOT group over the subsequent period. The central fovea, and outer retinal layer thickness in the HBOT group were significantly greater than those in the control group at the 6-month follow-up after treatment. HBOT appears to be effective in improving VA and inducing favorable changes in OCT parameters in patients with CRAO. It helps to preserve retinal layer thickness, especially in the outer retinal layer.